Cidade, gênero e sexualidade: territorialidades LGBT em Uberlândia, MG - Freitas, Bruno de (2016)
This work aimed to study the urban role in the establishment of territoriality especially designed to the group formed by Lesbians, Gays, Bisexuals and Transgender (LGBT), in the central sector of Uberlandia, Minas Gerais, in the light of issues related to gender and sexuality, leisure and/or tour consumption of this market segment as well as the influences of cyberspace. In addition, it aimed to understand how the government and Non-Governmental Organizations (NGOs) work to the inclusion of this social minority. From a geographical point of view, this research is justified by the necessity to understand how the consolidation of multiple LGBT territories occurs, as this topic is academically little discussed, particularly in the field of Geography. To develop the proposed study, it is based on a geographical perspective to look at the contemporary issues of gender and sexuality, as researches in this area are not expressive in the Brazilian scientific and geographic production. Regarding the methodology, documentary studies and literature review were conducted, as well as the cartographic survey, to the phenomena could be spatialized and interpreted. In field, direct observation and information collection were made through free testimonial. In addition to the research carried out directly in the leisure places preferentially destined to members that integrate LGBT group, Uberlandia public entities and representatives of NGOs were visited. It was necessary to verify how they think the guarantee of rights to that group through statutes and specific legislation, contributing to the socioeconomic development of the members of this social minority. According to the results, it is recognized that it is indispensable to start developing a Geography that makes possible the thinking of a complex space composed of several different and simultaneous processes, in order to highlight the relativity of scales of spatial approaches. Moreover, it was found that Uberlandia has heterogeneity and complexity that territorially manifest in urban areas, contributing to the generation of distinct territorialities by aspects linked to the prejudice, because of numerous factors.